(untitled) (SAARC Journal of Agriculture, 2022)
The purpose of this study was to observe the germination rate and fungal pathogens association in selected Tossa jute varieties. The experiment was conducted following Completely Randomized Design (CRD) with four replications. Truthfully labelled seeds (TLS) collected from four districts in Bangladesh, was used in the present study. The Highest germination rate (93.5%) and the lowest infection (31.25 pathogens/100 seed) were observed in BJRI Tossa Pat 5 (O-795) variety. BJRI Tossa Pat 4 (O-72) was observed as the most vulnerable against pathogen infection (121.25 pathogens/100 seed) and the showed lowest germination (83.25%). Regressions co-efficient (β) -0.82 was observed between germination (%) and total number of pathogens on seeds. Regression co-efficient (β) was -0.71 between moisture (%) and germination (%) of Tossa seeds. Regression co-efficient (β) was 0.65 between moisture (%) and total number of pathogens at Tossa jute seeds. For conducting the experiment, there was no limitation. From the study, it may be concluded that, seed-borne pathogenic fungi negatively affect the germination (%) of Tossa jute seed. SAARC J. Agric., 20(1): 67-76 (2022)